REVIEW: Perkembangan Sel Surya Perovskite - Noto Susanto Gultom; Ihsanul Mubarok; Hafsah Mutmainnah; Wina Mardhatillah; Ayi Bahtiar; Richie Estrada; Aisyah Amirah Fathinah (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
Perovskite is one of the materials used for solar panels that offers high efficiency comparable to conventional silicon-based solar cells. This article aims to analyze the latest developments in perovskite solar cells from various important aspects, starting from material development, various fabrication techniques, as well as opportunities and challenges in its development. Perovskite is a type of material that has a crystal structure with the chemical formula ABX3. Perovskite fabrication can be done using various methods such as spin coating, spray coating, doctor blading, inkjet printing and others. In its development, various innovations have been made, such as the development of cells without a hole transport layer (HTL-free), the addition of ethylenediammonium cations (en), and efforts to replace lead with more environmentally friendly materials such as tin. The results of the study showed that the power conversion efficiency (PCE) of perovskite solar cells has reached more than 25%. Although this development is promising, there are still major challenges in maintaining the long-term stability of the device, especially related to degradation due to humidity, heat, and prolonged lighting. The development of fabrication techniques that can mass produce perovskite solar cells with high performance and stable reliability is essential. With continued research and material innovation, perovskite solar cells have great potential in supporting sustainable clean energy transitions such as their applications in building-integrated photovoltaic (BIPV) systems, wearable electronic devices, and agrivoltaic systems.